Pengaruh Model Make A Match terhadap Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam Di Sekolah Dasar - Rochim, Ahmad Abdul (Cipta Media Harmoni, 2025)
Abstract— This study aims to evaluate the impact of the Make a Match learning model using card pair media on the Islamic Religious Education learning outcomes of third-grade students at an elementary school. The population in this study consists of third-grade students at SDIT Nurul Imam for the 2023/2024 academic year in Majalaya District, Karawang Regency, with a simple random sampling technique used for sampling. The research was conducted in the third-grade classes at SDIT Nurul Imam, with Classes III A and B serving as the experimental group, and Classes III C and D as the control group. The independent variable in this study is the implementation of the Make a Match learning model using card pair media, while the dependent variable is the learning outcomes in Islamic Religious Education. Data collection was carried out through both test and non-test methods, including observation sheets, documentation, and post-tests. The collected data were analyzed using quantitative analysis techniques, such as calculating the mean, standard deviation, normality tests, homogeneity tests, and the Mann-Whitney U test. The results indicate that the Make a Match learning model with card pair media has an effect on students' Islamic Religious Education learning outcomes, as shown by the average post-test score of 84.24 in the experimental class, compared to 79.40 in the control class. In conclusion, the implementation of the Make a Match learning model is proven to be effective in improving the Islamic Religious Education learning outcomes of third-grade students at SDIT Nurul Imam in Majalaya District, Karawang Regency.